A Multidisciplinary Approach to Children with Speech Delay and Its Implications for Primary Care: A Narrative Review - Ni Made Ayu Mulia Kusuma Wardani; Putri Kartika Sari (Jurnal EduHealth, 2026)
Speech delay is a common developmental issue in early childhood that can impact communication skills, social interactions, and learning readiness. This article aims to review the basic concepts of speech delay, the principles of early intervention, the collaborative role of various professions in improving children's communication and social participation, and its implication to primary care. This study focused on a narrative review of several database sources, such as Google Scholar, PubMed, and Scopus. The results of the narrative review indicate that speech delay cannot be treated by a single professional. A collaborative approach involving pediatricians, physiatrist, speech therapists, occupational therapists, psychologists, and other rehabilitation professionals provides a more comprehensive picture of a child's needs. Speech delay can be triggered by a combination of biological factors, lack of stimulation, and increased use of gadgets. The role of healthcare professionals in conducting routine screenings, providing education, and determining referral needs is crucial because most cases are first identified in primary healthcare settings. Language stimulation at home with parental involvement has also been shown to be a strong supporting factor. Interventions initiated at a younger age, particularly before the age of five, yield better developmental outcomes due to the child's still-developing brain's ability to adapt.